Nanostructuring during crystallization of cast aluminum‑copper‑silicon alloys and their structural stability during remelting - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
The main structural elements of melts of foundry aluminum‑copper‑silicon alloys are elementary nanocrystals of aluminum, copper, silicon and their free atoms. The main crystallizing phases of these alloys are microcrystals of α‑phases, silicon and θ‑phases. The process of their crystallization is nanostructural. First, structure‑forming nanocrystals are formed from elementary nanocrystals and free atoms. Then the centers of crystallization of microcrystals of phases are formed from them. From them, the structure‑forming nanocrystals of m free atoms of aluminum, copper, and silicon, microcrystals of α‑phases, silicon, and θ‑phases are formed. It is shown that the structural stability during remelting of cast aluminum‑copper‑silicon alloys is inversely proportional to the concentrations of adsorbed hydrogen and oxygen atoms.